Kinerja Saham PT Aqua Golden Mississippi Tbk. Setelah Pembatalan Go Private dan Estimasi Harga Saham Aqua Tahun 2010 - Putri, Indah Wandita; Heykal, Mohamad (Bina Nusantara University, 2010)
PT Aqua Golden Mississippi is a company that plans to go private, but until today have not obtained approval from the shareholders. Failure may be caused from several things: the company offer price is too small, no quorum, shares held is still profitable for shareholders, and other factors. The existence of the companys plan to go private would affect the performance of the company stock. Stock performance can be analyzed with - average rate of profit, the level of risk, and sensitivity to the stock exchange. The method used in the calculation of stock performance in this paper is the GMR, STDEV, CAPM, and DDM for the calculation of estimated stock price. Through the conducted analysis, investors / shareholders are encouraged to pay attention to the news and information related to go private to be conducted by the company, stock performance, and perform estimate calculations. This is to find out what the right decision for private investors.Â